Bahasa Ibu dalam Arus Modernitas: Analisis Filsafat Bahasa Ludwig Wittgenstein terhadap Praktik Bahasa Manggarai-Flores - Felix Riondi Sugar; Liberius Febri Naro; Marselinus Langgor; Falentinus Carles; Adelberto Wili Boko; Iluminata Fatreimin Adur; Arnoldus Roy Alfander (STIKAS Santo Yohanes Salib Kalimantan Barat, 2026)
This study aims to analyze the existence of the Manggarai-Flores mother tongue amidst the tide of modernity using Ludwig Wittgenstein’s philosophy of language. The mother tongue is understood not only as a tool for communication but also as a medium for shaping meaning, identity, and the sociocultural practices of a community. The research method employed is a qualitative approach using a literature review, examining various works related to the philosophy of language, mother tongues, and the Manggarai language. The findings indicate that the Manggarai language serves a complex function as a living system of meaning embedded in the daily practices of the community. From Wittgenstein’s perspective, the meaning of language is determined by its use within the context of everyday life (language games). This is evident in Manggarai cultural practices such as traditional rituals, oral literature, and daily communication, which are rich in social and cultural values. However, technological advancements and the dominance of national and global languages have led to a shift in the use of the mother tongue, particularly among the younger generation. Thus, the Manggarai language faces not only the threat of linguistic extinction but also the potential loss of cultural identity. Therefore, the preservation of mother tongues must be achieved through their integration into education, the strengthening of cultural literacy, and the revitalization of language use in the social life of the community.